Zoysiagrass for Florida Lawns - Bryan Unruh; Marco Schiavon; Alex Lindsey; Kevin Kenworthy; Laurie Trenholm (EDIS)
Zoysiagrasses were introduced into the United States from Asia and provide attractive turf throughout much of the United States. In recent years, newer cultivars of zoysiagrass have entered the market with improved insect resistance, accelerated establishment, and better overall performance. This 8-page major revision of the Environmental Horticulture Department was written by J. Bryan Unruh, Marco Schiavon, Alex J. Lindsey, Kevin E. Kenworthy, and L. E. Trenholm. https://edis.ifas.ufl.edu/lh011